2008
DOI: 10.5733/afin.049.0204
|View full text |Cite
|
Sign up to set email alerts
|

Three New Genera of Tracheline Sac Spiders from Southern Africa (Araneae: Corinnidae)

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 11 publications
1
49
0
Order By: Relevance
“…Lehtinen (1996: 409) has already referred to the group as Trachelidae, but without any comment of justification; hence, it is unclear whether he really meant to propose it as a new family group, or he just committed a lapsus. Platnick and Ewing (1995) noted that the absence of leg spines and the male cusples were not universal in trachelines, and Haddad (2006) described Spinotrachelas capensis, a tracheline genus with many spines on their anterior tibiae, plus cusples on the metatarsus, and later (Haddad and Lyle, 2008) described Poachelas, including species with heavily spinose forelegs, that could be absent in females of some species. They reasonably suggested that Spinotrachelas and Poachelas, by their abundant spines, could be basal trachelines.…”
Section: Eutichuridae Lehtinen New Rankmentioning
confidence: 99%
See 1 more Smart Citation
“…Lehtinen (1996: 409) has already referred to the group as Trachelidae, but without any comment of justification; hence, it is unclear whether he really meant to propose it as a new family group, or he just committed a lapsus. Platnick and Ewing (1995) noted that the absence of leg spines and the male cusples were not universal in trachelines, and Haddad (2006) described Spinotrachelas capensis, a tracheline genus with many spines on their anterior tibiae, plus cusples on the metatarsus, and later (Haddad and Lyle, 2008) described Poachelas, including species with heavily spinose forelegs, that could be absent in females of some species. They reasonably suggested that Spinotrachelas and Poachelas, by their abundant spines, could be basal trachelines.…”
Section: Eutichuridae Lehtinen New Rankmentioning
confidence: 99%
“…225, table 33). Haddad and Lyle (2008) and Haddad (2006) suggested that the tracheline genera Poachelas and Spinotrachelas might be the most basal members of the family because they retained fully developed leg spines. They also suggested that genera such as Fuchiba and Fuchibotulus, which lack both spines and cusps even in males, should be among the most-derived trachelids.…”
Section: Trachelidaementioning
confidence: 99%
“…often provides considerable numbers of these spiders. Initially, Poachelas striatus Haddad & Lyle was described from only three localities in the central Free State (Haddad & Lyle, 2008), but hand collecting in grass tussocks elsewhere in the country resulted in many additional records from the Free State, as well as the first records from the Northern Cape, Eastern Cape and Mpumalanga, extending the distribution of the species to more than 900 km (Haddad, 2010).…”
Section: Microhabitat Utilisation and Preferences Plant- Litter-and mentioning
confidence: 99%
“…Although most genera in this subfamily resemble ants, Copa species have cryptic colouration and closely resemble wolf spiders of the family Lycosidae (Figs 1–6), a characteristic shared with Echinax and two undescribed lycosiform castianeirine genera (Haddad 2012a, b, in prep.). Copa are very common spiders in the leaf litter of various habitats and are predominantly ground-living, occurring widely in savanna woodlands but also occasionally in forests, where they are well camouflaged.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to this revision, seven species and one subspecies of Copa were known from the Afrotropical Region (Dippenaar-Schoeman and Jocqué 1997), of which one described by Simon (1909) has been transferred to Echinax (Haddad 2012a). Another species, described by Strand (1916), will be transferred to a new castianeirine genus (Haddad 2012b in prep. ).…”
Section: Introductionmentioning
confidence: 99%